2004
DOI: 10.1002/j.2334-4822.2004.tb00409.x
|View full text |Cite
|
Sign up to set email alerts
|

11: Foucault and the Practice of Educational Development: Power and Surveillance in Individual Consultations

Abstract: A common goal ofeducational development isto create a neutral. "safi"place for clients in individualconsultations. Such an approach. while well intentioned. obscures the multiftceted web ofpower threading through and around our work. Using Michel Foucault's theories ofsovereign and disciplinary power, we trace the flnns that power can takein specific types ofconsultations (small group instructionaldiagnosis. course evaluations. and videotape). While power isalways "dangerous•..it is less likely to bedamaging i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…We define authenticity as referring, 'to an inner self that can recognize performative demands and act knowingly and mindfully in response to them' (MacKenzie, McShane, & Wilcox, 2007, p. 47), drawing on Ball's (2000) definition of performativity. We agree with Felten, Little, and Pingree (2004), when they warn against the widely held illusion that a consultation can be 'value-free, neutral, unimpeded, or not substantially shaped by power dynamics' (p. 182), and argue that authenticity and ethical interaction, not neutrality, should be the ideal we pursue. We will consider seven mental models employed by developers in their consultations with academics and discuss how conscious consideration of a developer's orientation (Land, 2001), allegiance, and intention can assist in the achievement of more authentic one-to-one interactions with academics.…”
Section: Introduction: the Myth Of Neutralitymentioning
confidence: 70%
See 1 more Smart Citation
“…We define authenticity as referring, 'to an inner self that can recognize performative demands and act knowingly and mindfully in response to them' (MacKenzie, McShane, & Wilcox, 2007, p. 47), drawing on Ball's (2000) definition of performativity. We agree with Felten, Little, and Pingree (2004), when they warn against the widely held illusion that a consultation can be 'value-free, neutral, unimpeded, or not substantially shaped by power dynamics' (p. 182), and argue that authenticity and ethical interaction, not neutrality, should be the ideal we pursue. We will consider seven mental models employed by developers in their consultations with academics and discuss how conscious consideration of a developer's orientation (Land, 2001), allegiance, and intention can assist in the achievement of more authentic one-to-one interactions with academics.…”
Section: Introduction: the Myth Of Neutralitymentioning
confidence: 70%
“…In this context the developer's job is to tactfully extract what amounts to a confession (MacFarlane & Gourlay, 2009), in which the teacher admits to committing certain mistakes and relates a critical incident that caused the teacher to embark on change, concluding with a plan to introduce new scripts into his or her teaching repertoire that will align more closely with currently approved attitudes and behaviors. The opportunity to record in writing his or her own perspective ostensibly lessens the teacher's resistance to surveillance, providing a way for the teacher to share disciplinary power, in the Foucauldian sense of self-surveillance (Felten et al, 2004), over him-or herself.…”
Section: Mental Modelmentioning
confidence: 99%
“…They feel EDs must remain critical and aware of what discourses they are forwarding and sustaining, and that these are not bias-free or neutral. Felten et al (2004) counsel critical consciousness as a means to resist institutional agendas and promote an authentic approach. Holmes et al (2012) forward the metaphor of EDs as a middle power country, like Canada and Australia, in that although said countries lack the influence and resources of some great power countries, they are still able to leverage change through creativity, collaboration, and cooperation.…”
Section: Challengesmentioning
confidence: 99%
“…For example, Little and Green (, 206–207) found that developers they interviewed often struggled with the bluntness of the word “power,” preferring instead to talk of “institutional visibility,” “clout,” and “influence.” While this reluctance may be in part cultural, some of the examples cited by Little and Green describe an intentional separating of educational development from “official” power, such as evaluative power over faculty. However, just as there are real implications for the power we lack, we must be aware of the power that we can—and do—exercise over others (Brookfield ; Felten, Little, and Pingree ). And this is why we need to understand how power works in our field in an intersectional way, because single‐axis approaches “fail to interrogate or interrupt, and thereby perpetuate, systems of domination and subordination” (Greenwood , 28).…”
Section: Intersections Of Powermentioning
confidence: 99%